Політика структурної економічної оптимізації в конвергентній моделі розвитку регіону - Жовтанецький, В.І.; Заблоцький, Б.Ф. (Економіка промисловості, 2013)
Обґрунтовано концепцію конвергентної моделі розвитку регіону в системі структурної перебудови національної економіки. Визначено пріоритети політики уряду, обласних державних адміністрацій і підприємств щодо збалансованого узгодження їх інтересів. Зроблено акцент на формування економічної самодостатності регіонів як основи становлення конвергентної моделі функціонування національної і регіональної економіки.
Ключові слова: структура економіки, економіка регіону, економічна політика уряду, регіональна економічна політика, ефективна діяльність підприємств, баланс інтересів. Обоснована концепция конвергентной модели развития региона в системе структурной перестройки национальной экономики. Определены приоритеты политики правительства, областных государственных администраций и предприятий по сбалансированному согласованию их интересов. Сделан акцент на формирование экономической самодостаточности регионов как основы становления конвергентной модели функционирования национальной и региональной экономики.
Ключевые слова: структура экономики, экономика региона, экономическая политика правительства, региональная экономическая политика, эффективная деятельность предприятий, баланс интересов. he concept of convergent model of regional development in the system of structural restructuring of the national economy is grounded. It is emphasized that the region in the form of territorial-administrative organization of management is an organized part of Ukraine functioning on the basis of objective economic laws, the legislation of the state, and central government decisions. The priorities of the government policy are defined, in particular selection of personnel from management macroeconomic financial and investment processes, programming and strategic planning of development of Ukraine and its regions, formation of innovation and investment resources and their protectionguarantees. Staffing from management by the region, finance and investment in the region, formation of targeted regional programs for industries and special economic zonesdevelopment, investment in regional scientific potential and specialization of production are the priorities of policy of regional state administrations. Regional companies carry out policies of training and attraction of experts in management by enterprises, corporations, and cooperatives, making business plans for enterprises development in competitive environment, investing in restructuring of capital, labor and product, and the protection of nature. Production results of consistent policies government, regions and enterprises are proved: rising productive labor, capital returns, and production efficiency, reducing the total cost.The price stability, reduction of budget deficits of government and Ukraine's regions, reduction of the rate of intermediate consumption, and growth of value added norm are among the expected financial results.
Keywords: structure of economy, economy of region, economic policy of government, regional economic policy, effective activity of enterprises, balance of interests.